A Methodology Report for the Life’s Snapshot Cohort Study to Investigate the Long-Term Efficacy of a Violence Intervention - Coker, Ann L. (Violence against women, 2022)
Engaged bystander interventions are recognized as “promising” programming to reduce sexual violence (SV), yet little is known of the long-term (>12-month) impact of programming on SV and related forms of gender-based violence. Funded by NIH as a prospective cohort study, Life’s Snapshot recruited and followed three waves of high school seniors who had participated in a large high-school cluster-randomized controlled trial to evaluate the effectiveness of the Green Dot bystander intervention. This report provides the study design, recruitment methodology, recruitment and retention rates, survey items, and psychometric properties of measures included in the initial and annual electronic surveys with 24–48 months follow-up.